New opportunities to valorize biomass wastes into green materials. (1st October 2016) - Spiridon, Iuliana; Darie-Nita, Raluca Nicoleta; Hitruc, Gabriela Elena; Ludwiczak, Joanna; Cianga Spiridon, Irene Alexandra; Niculaua, Marius
Abstract: Due to depleting natural resources, new environmental regulations and economic considerations, there is a constantly growing interest in using renewable resources. That is why, considering the growing awareness of environmental and waste management issues, green composites are increasingly promoted for sustainable development. Novel materials based on polylactic acid and different biomass wastes have been obtained and analyzed. The addition of biomass to a polylactic acid matrix resulted in more opaque materials, with decreased values of the water contact angle and acceptable values of mechanical properties. Thus, transparency decreased from 1.99 for polylactic acid to 0.94 for the material comprising pomace fibers. Asclepias syriaca fibers and celery root fibers determined a decrease in the water contact angle of about 9%, while pomace fiber led to a decrease of 3% and poplar seed hair fibers – of 7%. The addition of A. syriaca fibers into the polylactic matrix (as reference) resulted in a decrement of 42% in tensile strength and an increment of 10% in impact strength. Dynamic vapor sorption studies have indicated that sorption capacity increased by 86%. The material comprising poplar seed hair fibers recorded a decline of 45% in tensile strength and an improvement of 20% in impact strength, while water sorption capacity increased by 83%. The pomace fibers resulted in a drop of 56% in tensile strength and an improvement of 18% in impact strength. The presence of celery root fibers in the polylactic acid matrix contributed to a decrease of 53% in tensile strength and of 37% in impact strength. The last two fillers determined the most significant increase in water sorption capacity, 266% for the material comprising pomace and 210% for the one containing celery root fibers. The biomass residues under study represent sources of raw material that proved suitable for manufacturing new materials, which could reduce domestic dependence on petroleum-based thermoplastics. Highlights: Novel materials based on PLA and different biomass wastes have been obtained. Materials have presented higher opacity and lower contact angle as compared with PLA matrix. All composites showed acceptable mechanical properties. Presence of biomass increased the water sorption capacity of materials.